Assessment and Potential of Carbon Storage Capacity of Species of Herbaceous Plants in Universiti Tun Hussein Onn Malaysia, Main Campus, Batu Pahat, Johor Malaysia - Audu, Yunusa; Linatoc, Alona C.; I, Aisha (International Journal of Engineering and Technology, 2018)
Carbon dioxide CO2 is an important trace gas in earth's atmosphere. It is a greenhouse gas that plays a vital role in regulating the earth's surface temperature through the greenhouse effect. Increase beyond the ambient concentration leads to global warming. Increase in CO2 discharge in UTHM (238.9 ha), due to increase in a number of vehicles; other greenhouse gases released from building amenities and dis-charges from neighbouring industries appeals for attention. Study was conducted on seven common species of herbaceous plants for their capacity in sequestering CO2. Estimation of carbon storage of herbaceous plants was obtained by the assessments of the aboveground standing biomass and their photosynthetic capacity. Musa sp has the highest CO2 absorption of 12.2µmol m-2 s-1, followed by Heliconia. psittacorum (10.63µmol m-2 s-1). Euphorbia tithymaloides and Costus spicatus has the lowest absorption with 3.63 and 3.76 µmol m-2 s-1 respectively. Calathea lutea and Hymenocallis latifolia shared the highest biomass accumulation of 0.04 kg. These were followed by E. tithymaloides and Alpinia purpurata with 0.02 kg. The least biomass of 0.01 kg was accumulated by H. psittacorum and C. spicatus. The total standing biomass captured by all the species of herbaceous plants is 0.13 kg. Therefore, species of herbaceous plants in UTHM have the potentials to absorb an adequate amount of CO2 from the atmosphere thereby contributing to reducing-the effects of localized global warming.